Morphometric And Meristic Aspects of Lemuru Fish (Sardinella lemuru) Landed on Pancer Beach Banyuwangi - Dea Yolanda Aulia Rida; Karnan Karnan; Didik Santoso (Jurnal Biologi Tropis, 2026)
Lemuru fish (Sardinella lemuru) is the main small pelagic commodity in the Bali Strait that has high economic value but is vulnerable to pressure on the surface. This study aims to analyze the morphometric and meristic characteristics of lemuru fish landed on Pancer beach, Banyuwangi. The research method used a descriptive survey with stratified random sampling techniques of 50 individuals in the period from October to December 2022.  The results of measurements on 23 morphometric variables showed that the total length was 9 ≤ 19 cm (92%), the standard length was 7 ≤ 17 cm (86%), the body width was 1 ≤ 11 cm (90%), the height of the body was 2 ≤ 10 cm (88%), the height of the tail rod was 1 ≤ 9 cm (84%), the length of the tail rod was 1 ≤ 9 cm (96%), the length of the ventral fin was 1 ≤ 9 cm (90%),  Pectoral fin length 1 ≤ 13 cm (98%), Eye diameter 1 ≤ 9 cm (90%) and weight 10 ≤ 24 g (98%). Meanwhile, the calculation of 14 meristic variables of lemuru fish showed that: Number of Hard Dorsal Radius 2 ≤ 12 (88%), Number of Weak Dorsal Radius 3 ≤ 13 (96%), Number of Hard Anal Fin Fingers 2 ≤ 6 (86%), Number of Weak Anal Fin Fingers 2 ≤ 8 (88%), Number of Scales on Lateral Stripes 54 ≤ 67 (78%), Number of Scales Around the Body 33 ≤ 41 (60%), Number of Scales on Side Lines 5 ≤ 17 (94%),  The number of scales below the side line is 10 ≤ 20 (94%).